Peran Kepuasan Konsumen dalam Memediasi Pengaruh Kualitas Pelayanan, Prefensi Merek, dan Harga terhadap Repurchase Intention - Lisa Noviatri; Kasmita Kasmita (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research was motivated by the phenomenon of guest repurchase intention allegedly due to the quality of service, brand preferences, and prices at Warung Nasi Kelok Desa Talogondan. This study aims to analyze the role of satisfaction in mediating the effect of service quality, brand preference, and price on repurchase intention in Warung Nasi Kelok Talogon Village and Padang Pariaman Regency. This type of research is quantitative research with a causal associative approach. The population in this study is rice stall consumers who have visited Warung Nasi Kelok Talogon Village and Padang Pariaman Regency with a sample of 222 respondents. The research instrument used in this study was a questionnaire (questionnaire) arranged according to the Likert scale. Instrument trials use validity tests, reliability tests. Data analysis technique using Structural Equation Modeling with Partial Least Square (SEM-PLS). The result of the study is that there is a positive and significant influence between service quality variables and consumer satisfaction variables. There is a positive and significant influence between brand preference variables and consumer satisfaction variables. There is a positive and significant influence between price variables and consumer satisfaction variables. There is a positive and significant influence between the consumer satisfaction variable and the repurchase intention variable. There is an influence of customer satisfaction as a positive and significant mediating variable between service quality and repurchase intention. There is an influence of consumer satisfaction as a positive and significant mediating variable between brand preference for repurchase intention and path coefficient. There is an influence of consumer satisfaction as a positive and significant mediating variable between price and repurchase intention and path coefficient.